Religiosity in Mustofa Bisri's Collection of Lukisan Kaligrafi Short Story - Ali Azizi, Fakhri; Nuryatin, Agus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Lukisan Kaligrafi comes as a literary work that is thick in the value of religiosity, transcendent, teaching about religious social life, both vertical and horizontal. The objectives of this study are to describe religiosity in a collection of Lukisan Kaligrafi short stories, to analyze the correlation between religiosity and social reality, and to reveal the author's point of view of religiosity. The researcher used the approach of structuralism and literary sociology in this research. The method used is the hermeneutic method, which is to turn and reconstruct a text in a bound of interactions between the author and the reader. The results of the study (1) the dimension of belief or ideology, (2) the dimension of religious practice or worship, (3) the dimension of religious experience, (4) the dimension of religious knowledge, and (5) the dimension of consequence. There are several attitudes described in describing the correlation of short story religiosity with social reality, among others are: (1) education, (2) peace, (3) Social supervision, (4) worship of solidarity, (5) transformative, (6) creative, (7) sublimative, (8) harmony, (9) emotionally religious, and (10) tolerance.